Simulation of rock infiltration systems - Wilson, Bruce N.; Sheshukov, Aleksey Y.; Mendez, Aida (My University, 2015)
Rain gardens, infiltration trenches, and dry detention ponds are widely used to treat runoff from construction site and urban watersheds. These infiltration systems have the potential to remove contaminants by filtration, but they also may become clogged with deposited sediment and other debris. An overview of studies done at the University of Minnesota over the past 10 years to investigate the trapping of sediment and the corresponding changes in permeabilities is presented. They include experimental data collected from the laboratory cores, a prototype dry detention basin, and field studies as well as the development of algorithms used in the WATER (Watershed Assessment Tool for Environmental Risk) model.
Keywords: Rain garden; Infiltration; Urban; Stormwater